Impact of tranexamic acid on hidden blood loss in intertrochanteric fractures: a meta-analysis of randomized controlled trials - Meng, Yan; Zhang, Yong; Xue, Hanzhong; Duan, Ning; Li, Zhong; Wang, Qian; Lu, Yao (Frontiers in Surgery, 2025)
BackgroundIntertrochanteric fractures (IFs) are a common type of fracture in the elderly and are often associated with substantial hidden blood loss (HBL) due to trauma and surgery. Tranexamic acid (TXA) has emerged as a potential intervention to reduce perioperative bleeding. This study aimed to evaluate the safety and efficacy of TXA administration in elderly patients with IFs undergoing intramedullary nailing, through a systematic review and meta-analysis of randomized controlled trials (RCTs).MethodsWeb of Science, Cochrane Library, Embase, and PubMed were searched for relevant RCTs published from inception to January 2025. Data on HBL, total blood loss (TBL), transfusion rate, and thromboembolic events were extracted. Review Manager 5.3.5 was used to assess the safety and efficacy of TXA.ResultsEight RCTs involving 735 patients (363 in the TXA group and 372 in the control group) were included in the meta-analysis. The TXA group demonstrated significantly lower HBL [standard mean difference (SMD) = −0.59; 95% confidence interval (CI), −0.74 to −0.45] and TBL (SMD = −0.74; 95% CI, −0.91 to −0.58), as well as a reduced transfusion rate [relative risk (RR) = 0.50; 95% CI, 0.35–0.72] compared with the control group. Additionally, no significant difference in thromboembolic events was found between the two groups.ConclusionsCurrent evidence indicates that TXA significantly reduces HBL and transfusion requirements without increasing the risk of thromboembolic events in elderly patients with IFs.